Non-coding transcriptomic profiles in the sheep mammary gland during different lactation periods - Chen, Weihao; Gu, Xinyu; Lv, Xiaoyang; Cao, Xiukai; Yuan, Zehu; Wang, Shanhe; Sun, Wei (Frontiers in Veterinary Science, 2022)
Sheep milk production is a dynamic and multifactorial trait regulated by diverse biological mechanisms, in order to enhance the quality and production of milk in sheep, it is necessary to examine the underlying non-coding transcriptomic mechanisms. In the present study, RNA-seq was performed to profiled the expression of miRNAs and circRNAs in sheep mammary gland during three key time points of lactation (perinatal period, PP; early lactation, EL; and peak lactation, PL). We profiled a total of 2,369 novel circRNAs and 272 miRNAs, within which, 348, 373, and 36 DE circRNAs, as well as 30, 34, and 7 DE miRNAs were detected in EL vs. PP, PL vs. PP, and PL vs. EL comparison, respectively. By applying a serious of bioinformatic analyses including functional enrichment, machine learning prediction, ceRNA network analysis, subsets of potential candidate miRNAs (e.g. oar_miR_148a, oar_miR_362, oar_miR_432) and circRNAs (e.g. novel_circ_0011066, novel_circ_0010460, and novel_circ_0006589) for sheep mammary gland development were identified. Taken together, our present study offers a window into the non-coding transcriptomic dynamics that occur during sheep lactation, and may provide further insights on the roles of miRNA and circ RNA in sheep mammary gland development.